FLU: A negative regulator of chlorophyll biosynthesis in Arabidopsis thaliana - Meskauskiene, Rasa; Nater, Mena; Goslings, David; Kessler, Félix; Den Camp, Roel Op; Apel, Klaus (My University, 2001)
Tetrapyrroles such as chlorophylls and bacteriochlorophylls play a fundamental role in the energy absorption and transduction activities of photosynthetic organisms. Because of these molecules, however, photosynthetic organisms are also prone to photooxidative damage. They had to evolve highly efficient strategies to control tetrapyrrole biosynthesis and to prevent the accumulation of free intermediates that potentially are extremely destructive when illuminated. in higher plants, the metabolic flow of tetrapyrrole biosynthesis is regulated at the step of delta -aminolevulinic acid synthesis. This regulation previously has been attributed to feedback control of Glu tRNA reductase, the first enzyme committed to tetrapyrrole biosynthesis, by heme. With the recent discovery of chlorophyll intermediates acting as signals that control both nuclear gene activities and tetrapyrrole biosynthesis, it seems likely that heme is not the only regulator of this pathway. A genetic approach was used to identify additional factors involved in the control of tetrapyrrole biosynthesis. In Arabidopsis thaliana, we have found a negative regulator of tetrapyrrole biosynthesis, FLU, which operates independently of heme and seems to selectively affect only the Mg2+ branch of tetrapyrrole biosynthesis. The identity of this protein was established by map-based cloning and sequencing the FLU gene. FLU is a nuclear-encoded plastid protein that, after import and processing, becomes tightly associated with plastid membranes. It is unrelated to any of the enzymes known to be involved in tetrapyrrole biosynthesis. its predicted features suggest that FLU mediates its regulatory effect through interaction with enzymes involved in chlorophyll synthesis.
Keywords: PHYTOCHROME-CHROMOPHORE BIOSYNTHESIS; MAGNESIUM CHELATASE; PROTEIN; IMPORT; CHLOROPLASTS; BARLEY; HEME; DEFICIENT; ENZYMES; PLANTS; IDENTIFICATION